2019
DOI: 10.24085/jsaa.v6i2.3307
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Attitudes and Perceptions on Xenophobia: A Study of a University in Durban

Abstract: The recurrence of xenophobic violence in South Africa has been attributed to the proliferation of antimigrant sentiments that stems from social, political, economic and cultural misconceptions and cleavages. The study presents the results of a survey undertaken at the Durban University of Technology (DUT) to investigate the perceptions and attitudes of DUT students on xenophobia in South Africa. A questionnaire was designed and employed to collect data from 547 registered students of a university in Durban. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…However, after the researcher probed more on this question, one of the participants hinted that this behaviour may be there even though it is suppressed by the students. This is synonymous with the findings by Akande et al 18 from their study conducted on students' attitudes and perceptions of xenophobia at a university in Durban, KwaZulu-Natal, because they found that despite the majority of students showing nonxenophobic perceptions, traces of xenophobic attitudes and perceptions were observed from some of the students. Moreover, similar findings emerged from a similar study 27 at the University of KwaZulu-Natal, where findings showed evidence of students perpetrating verbal xenophobic attacks on other African students.…”
Section: Students' Views On the Experiences Of Xenophobic Behaviour I...supporting
confidence: 65%
See 4 more Smart Citations
“…However, after the researcher probed more on this question, one of the participants hinted that this behaviour may be there even though it is suppressed by the students. This is synonymous with the findings by Akande et al 18 from their study conducted on students' attitudes and perceptions of xenophobia at a university in Durban, KwaZulu-Natal, because they found that despite the majority of students showing nonxenophobic perceptions, traces of xenophobic attitudes and perceptions were observed from some of the students. Moreover, similar findings emerged from a similar study 27 at the University of KwaZulu-Natal, where findings showed evidence of students perpetrating verbal xenophobic attacks on other African students.…”
Section: Students' Views On the Experiences Of Xenophobic Behaviour I...supporting
confidence: 65%
“…Other researchers like 15,18 and McDonald and Jacobs 16 have researched the print media's contribution to xenophobic violence in South Africa. Therefore, it was of interest in this article to also examine students' views on the influence of the media on xenophobic behaviour.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations